Developing civil society in Ukraine: What is the role of the mechanisms for implementing the association agreement with the EU? - Andrii Krupnyk (CES Working Papers, 2021)
The aim of this study is to assess the implementation of the principles of the Association Agreement between Ukraine and the European Union (hereinafter - the Agreement) in Ukraine in the field of civil society development, in particular in the implementation of the National Strategy for Civil Society Development for 2016-2020 (hereinafter - the National Strategy - 2020). A comparative analysis of ensuring in Ukraine the principles of stability and effectiveness of democratic institutions, rule of law, respect for human rights and fundamental freedoms, as agreed by the Parties to the agreement in the field of domestic policy. The analysis revealed certain deviations from the provision of these democratic principles. Requirements for the content of the new National Strategy, which is being formed for 2021-2026 (hereinafter - the National Strategy - 2026) by joint efforts of the Ukrainian government and civil society organizations (CSOs) have been formulated. Based on the study, specific recommendations were made on the implementation of the principles of the Agreement in the draft of the new National Strategy - 2026 and on the further development of civil society in Ukraine.
Keywords: 330; civil society; democratic principles; National Strategy; implementation mechanisms; intersectoral cooperation